Specialization in Entry-Level Products: A Strategy for Industrial Development in Africa - Diaw, Diadié; Lessoua, Albert; Ndione, Louis (Management international / International Management / Gestiòn Internacional)

(untitled) (HEC Montréal, 2020)
This article analyzes the potential of industrial development in Africa. Starting with the observation that the domestic demand in Africa is mainly oriented towards entry-level products, we explore the advantages of an industrialization strategy aimed at manufacturing these products. After identifying the determinants of specialization in entry-level products, we find that these product lines can play a fundamental role in the industrialization of Africa. It should also be noted that studies on entry-level products in Africa are quite rare; this study therefore opens up avenues for future research.